Effect of Temperature and Salinity on the Infectivity Pattern of White Spot Syndrome Virus (WSSV) in Giant tiger shrimp Penaeus monodon (Fabricius 1837) - Raj, Stalin; Vijayan, K. K.; Alavandi, S. V.; Balasubramanian, C. P.; Santiago, T. C. (Indian Journal of Fisheries, 2012)
White spot disease (WSD) caused by the lethal white spot syndrome virus (WSSV) continues to be the major cause ofmortality among farmed tiger shrimp in India and elsewhere, resulting in an annual loss of about 4-6 billion US. Among theenvironmental variables, temperature and salinity of the rearing water are considered to be major triggering factors for whitespot disease outbreak. In order to characterise the effect of salinity and temperature on the pathogenecity of WSSV infectionin giant tiger shrimp Penaeus monodon, a laboratory challenge study was conducted at different levels of temperature(16, 25, 27, 28, 30, 32 and 36 ºC) and salinity (0.5, 5, 10, 15, 30 and 45 g l-1) with virulent white spot syndrome virus.Significant influence of temperature (p<0.05) on the percentage mortality and time until death of shrimp affected by the viruswas observed, whereas salinity did not show any effect. Significantly higher survival rate was recorded in animalsexposed at 32 ºC (37%) and 36 ºC (14%), 21 days post-challenge (dpc). All the shrimp challenged at othertemperature levels, however, died after 21 dpc. These results demonstrated preference of WSSV for lower temperaturesand higher survival in temperature ranges of 32 ºC to 36 ºC. The present observation may help to develop amanagement option to control the WSSV inflicted mortalities by selecting favorable hyperthermic rearing conditions for theshrimp.